PENGARUH KEPUASAN KERJA TERHADAP INOVASI ORGANISASI MELALUI KREATIVITAS KARYAWAN - MARNIO PRATAMA, ERTANTO (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The purpose of this study was to analyze the influence of job satisfaction, organizational innovation and creativity in PT. Telkom region Surabaya. And the role of creativity in mediating the effect of job satisfaction on organizational innovation. Samples from this study were employees access division, consumer services, enterprise services, business services, telecom infrastructure, boardband division, and human resources department totaling 66 people. The data analysis technique used is the analysis of the alternative method of Structural Equation Model of Partial Least Square with the help of software SmartPLS 2.0 M3. The results of the study explained that job satisfaction significantly influence on organizational innovation. Job satisfaction significant positive effect on employee creativity. Creativity employees significantly influence on organizational innovation. Creativity employee job satisfaction mediates the effect of organizational innovation. Keywords: job satisfaction, organizational innovation, and creativity.